Clinical utility of p16/Ki67 dual‐stain cytology for detection of cervical intraepithelial neoplasia grade two or worse in women with a transformation zone type 3: A cross‐sectional study - Gustafson, Line Winther; Tranberg, Mette; Christensen, Pia Nørgaard; Brøndum, Rikke; Wentzensen, Nicolas; Clarke, Megan A.; Andersen, Berit; Petersen, Lone Kjeld; Bor, Pinar; Hammer, Anne (BJOG : an international journal of obstetrics and gynaecology, 2023)
Objective To evaluate the clinical utility of p16/Ki67 dual‐stain (DS) compared with cytology for detecting cervical intraepithelial lesion grade two or worse (CIN2+) in women with a transformation zone type 3 (TZ3). Design Cross‐sectional study. Setting Colposcopy clinics in Central Denmark Region. Population Women aged 45 years or older referred for colposcopy because of an abnormal screening test. Methods All women had a cervical sample collected for cytology and DS testing and underwent large‐loop excision of the transformation zone (LLETZ). Main outcome measure Sensitivity, specificity and negative (NPV) and positive (PPV) predictive values of DS for CIN2+ detection were compared to those of cytology. Results Of 166 women eligible, 93 (56.0%) were included in the final analysis. Median age was 68 years (interquartile range [IQR] 63.4–70.5 years). Most women were postmenopausal (95.7%) and referred based on a positive human papillomavirus screening test (86.0%). Fifty‐two women (55.9%) were DS‐positive, 29 (55.8%) of whom had CIN2+ detected. Twenty‐seven (29.0%) women had atypical squamous cells of undetermined significance or worse (ASC‐US+), and CIN2+ was detected in 21 women (77.8%). DS had a higher sensitivity (96.7% versus 70.0% p = 0.021) and NPV (97.6% versus 86.4%, p = 0.018) compared with cytology for CIN2+ detection. In contrast, the specificity (63.5% versus 90.5% p < 0.001) and PPV (55.8% versus 77.8%, p = 0.001) were lower for DS compared with cytology. Conclusions Dual stain may be a valuable risk marker to guide clinical management of women with a TZ3. The superior NPV of DS suggests that a diagnostic excision may safely be avoided in DS‐negative women. Tweetable DS‐negative postmenopausal women with a TZ3 have a low risk of CIN2+ and may undergo follow up instead of LLETZ.